Removal of selected heavy metals from green mussel via catalytic oxidation - Wan Abu Bakar, Wan Azelee (Universiti Kebangsaan Malaysia, 2014)
Perna viridis or green mussel is a potentially an important aquaculture product along the South Coast of Peninsular Malaysia especially Johor Straits. As the coastal population increases at tremendous rate, there was significant effect of land use changes on marine communities especially green mussel, as the heavy metals input to the coastal area also increase because of anthropogenic activities. Heavy metals content in the green mussel exceeded the Malaysian Food Regulations (1985) and EU Food Regulations (EC No: 1881/2006). Sampling was done at Johor Straits from Danga to Pendas coastal area for green mussel samples. This research introduces a catalytic oxidative technique for demetallisation in green mussel using edible oxidants such as peracetic acid (PAA) enhanced with alumina beads supported CuO, Fe2O3, and ZnO catalysts. The lethal dose of LD50 to rats of PAA is 1540 mg kg-1 was verified by National Institute of Safety and Health, United State of America. The best calcination temperature for the catalysts was at 1000 °C as shown in the X-Ray Diffraction (XRD), Nitrogen Adsorption (BET surface area) and Field Emission Scanning Electron Microscopy (FESEM) analyses. The demetallisation process in green mussel was done successfully using only 100 mgL-1 PAA and catalyzed with Fe2O3/Al2O3 for up to 90% mercury (Hg) removal. Using PAA with only 1 hour of reaction time, at room temperature (30-35°C), pH 5-6 and salinity of 25-28 ppt, 90% lead (Pb) was removed from life mussel without catalyst. These findings have a great prospect for developing an efficient and practical method for post-harvesting heavy metals removal in green mussel.